2016
DOI: 10.1002/ccd.26646
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous left atrial appendage occlusion: Effect of device positioning on outcome

Abstract: No evidence for a difference in the occurrence of the safety and efficacy endpoint was found between patients with complete vs. incomplete ACP disc coverage of the LAA ostium. The risk of repositioning attempts in case of incomplete coverage does not seem to be warranted. Current findings need further confirmation in a larger scale clinical trial. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…Concomitant closure of the patient’s foramen ovale was performed most frequently in the thromboembolism group, probably to avoid a further thromboembolism via a right-to-left shunt in this group with a history of recurrent thromboembolism. While Berti reported a much lower rate of concomitant procedures in the national Italian registry (2.4%) [ 21 ], the rate of combined procedures in our analysis (14.3%) was similar to other studies [ 22 , 23 ]. The procedural duration was similar to previous reports [ 20 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Concomitant closure of the patient’s foramen ovale was performed most frequently in the thromboembolism group, probably to avoid a further thromboembolism via a right-to-left shunt in this group with a history of recurrent thromboembolism. While Berti reported a much lower rate of concomitant procedures in the national Italian registry (2.4%) [ 21 ], the rate of combined procedures in our analysis (14.3%) was similar to other studies [ 22 , 23 ]. The procedural duration was similar to previous reports [ 20 , 24 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our data suggest that incomplete ostial coverage was associated with more MAE with the occurrence of pericardial effusion, tamponade, and neurological procedure‐related events which were founded in this group alone. However, these observations did not result in a significant difference between the groups with regards to long‐term clinical outcomes supporting results from a recent study evaluating outcomes after ACP implantation .…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, repositioning the device also can potentially increase risks of cardiac trauma . A recent study by Wolfrum et al demonstrated no differences in safety and efficacy end‐points in patients undergoing LAAC with the Amplatzer cardiac plug (ACP), the predecessor of the Amulet device, regardless of whether complete or incomplete ostium coverage was ultimately achieved. However, the Amulet proximal disc diameter is larger than that of the same size ACP device , and furthermore, the manufacturer recommends greater oversizing with new generation prosthesis .…”
Section: Introductionmentioning
confidence: 99%
“…A previous study of 169 consecutive patients evaluated the clinical outcome according to the position of the ACP disc [16]. There was no evidence of relevant differences in the incidence of devicerelated thrombi between patients with complete and incomplete disc coverage of the LAA ostium.…”
Section: Discussionmentioning
confidence: 90%